Neuropeptides in the antennal lobe of the yellow fever mosquito, Aedes aegypti. Issue 3 (15th February 2014) - Siju, K.P.; Reifenrath, Anna; Scheiblich, Hannah; Neupert, Susanne; Predel, Reinhard; Hansson, Bill S.; Schachtner, Joachim; Ignell, Rickard
<x xml:space="preserve">Abstract</x> For many insects, including mosquitoes, olfaction is the dominant modality regulating their behavioral repertoire. Many neurochemicals modulate olfactory information in the central nervous system, including the primary olfactory center of insects, the antennal lobe. The most diverse and versatile neurochemicals in the insect nervous system are found in the neuropeptides. In the present study, we analyzed neuropeptides in the antennal lobe of the yellow fever mosquito, Aedes aegypti, a major vector of arboviral diseases. Direct tissue profiling of the antennal lobe by matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) mass spectrometry indicated the presence of 28 mature products from 10 different neuropeptide genes. In addition, immunocytochemical techniques were used to describe the cellular location of the products of up to seven of these genes within the antennal lobe. Allatostatin A, allatotropin, SIFamide, FMRFamide‐related peptides, short neuropeptide F, myoinhibitory peptide, and tachykinin‐related peptides were found to be expressed in local interneurons and extrinsic neurons of the antennal lobe. Building on these results, we discuss the possible role of neuropeptide signaling in the antennal lobe of Ae. aegypti. J. Comp. Neurol. 522:592–608, 2014. © 2013 Wiley Periodicals, Inc.